Back Cover: A Molybdenum Disulfide Nanozyme with Charge‐Enhanced Activity for Ultrasound‐Mediated Cascade‐Catalytic Tumor Ferroptosis (Angew. Chem. Int. Ed. 11/2023). Issue 11 (6th February 2023) - Wang, Longwei; Zhang, Xiaodi; You, Zhen; Yang, Zhongwei; Guo, Mengyu; Guo, Jiawei; Liu, He; Zhang, Xiaoyu; Wang, Zhuo; Wang, Aizhu; Lv, Yawei; Zhang, Jian; et al.
Abstract : BTO/MoS2 @CA, with the integration of charge‐enhanced enzymatic activity, pH‐responsive CA release‐mediated H2 O2 self‐supply, and GSH depletion, enables out‐of‐balance redox homeostasis, leading to effective tumor ferroptosis. As demonstrated by Yawei Lv, Xin Yu, Jing Liu, Chunying Chen et al. in their Research Article (e202217448), charge is one of the important contributing factors for nanozyme activity, which has not been mentioned previously.